MULTI-WELL DRAINAGE AREA CALCULATION BASED ON DIFFUSIVE TIME OF FLIGHT: A NOVEL APPROACH FOR QUICK PRODUCTION FORECAST FOR CBM FIELDS - Rina, Buoy (Universiti Teknologi Petronas, 2012)
ABSTRACT For coalbed methane fields, selection of dynamic simulation models, namely, 3D numerical or analytical material balance (MB) is based on the scale and timeframe. At field scale and under reasonable timeframe, MB model is preferred to 3D numerical model due to its shorter turn-around time for simulation and results extraction. Conventionally, well drainage as the inputs for MB model is inferred from well spacing, which is unrealistic in heterogeneous media. In this study, end-of-transient well drainage areas are determined by Diffusive Time of Flights (DTOF) by employing numerical fast marching method (FMM) with the fine gridded property maps. Property up-scaling is performed in each well drainage. With drainage and average property information, full field production forecast is performed with MB model. To validate the proposed approach, results are compared against those of numerical model and conventional practice in which well drainage area is inferred from well spacing